ANALISIS BRAND SWITCHING HANDPHONE BLACKBERRY DI SALATIGA ( Studi Kasus Pada pengguna handphone Blackberry di STIE AMA Salatiga) - Putra, Yanuar Surya (AMONG MAKARTI, 2013)
Abstract Quality products at competitive prices is the key to winning the competition, which in turn will be able to give higher satisfaction to the customers. Customers now have demands much greater value and diverse because the customers are faced with a wide selection of products, goods or services that they buy. In this case the seller must provide a quality product that is acceptable, because if not, the customer will immediately switch to another similar product (brand switching), but basically brand switching behavior of consumers that do occur due to certain reasons such as: post-consumer dissatisfaction, pricing, advertising and looking for variations. The development of mobile phone business lately has shown a symptom, ie the abundance and diversity of products offered by mobile phone companies and mobile product development is getting faster. Rapid development of mobile products which are mainly located on the shape, size and amenities. The longer form of mobile phones more attractive, the smaller size and more complete utility facilities. Consumer buying process that involves decision-making , especially under conditions of limited decision making , will be positioned on the situation for the consumer variety seeking behavior . At the time of the low level of consumer involvement , consumers will tend to switch brands. RIM is the manufacturer of the Blackberry mobile phone , a mobile phone brand , which until recent years in Indonesia dominate mobile phone sales , but its dominance for some time began to decline , many consumer who did switching to another brand , especially when pricking the android operating system used , Blackberry It seems clear that a significant sales decline . From this background, which is the topic of this research are : Analysis Of Brand Switching On Blackberry Phone Salatiga ( Case Study On Blackberry mobile phone users in STIE AMA Salatiga ).The samples obtained in this research  were 88 people and to obtain a more in-depth analysis, factor analysis is needed to determine what factors that makes Blackberry mobile phone users in Salatiga AMA STIE brand switch to another brand of phone. From the analysis can be concluded that there are six factors causing the Blackberry mobile phone users in Salatiga AMA stie to switch to another brand of mobile phones, these factors are:(1) Comparison between the price and the benefits / features derived from Blackberry users are not comparable, (2)Curiosity to try other brands besides Blackberry phones.(3)Weariness to the Blackberry brand mobile phone, because there is no innovation and standard features.(4)Blackberry yet have maximum performance, frequent hangs and slow performance.(5) Blackberry has a lack of good quality hardware.(6) Blackberry mobile phone price comparison with other, more affordable brands but nicer features. Keywords : Brand Switching, Consumer Behaviour